(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The paper has three sections. First of all, the legal bases of Regulation (EU) No 650/2012 of the European Parliament and of the Council of 4 July 2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of succession and on the creation of a European Certificate of Succession are discussed, because this regulation shall be directly applicable in the Member States of European Union in accordance with the Treaties. There are several issues that fall outside the scope of the regulation, for example questions governed by the law of companies, such as clauses in the memorandum of association of companies, which determine what will happen to the shares upon the death of the members. From the point of view of Hungarian law, it is a matter of company law to talk about the inheritability of business shares in each type of companies. The second part of the paper is about general rules in company law regarding inheritance of business shares and in the third part family firms are discussed. Writing about these is common in Austrian legal literature; in connection with these, succession in family firms is a significant topic. In Hungarian legal literature the term family firm is rarely found, but the usage and content of term “family firm” cannot be neglected because of their role in economy.